Arecaceae Family in Gujarat, its Morphological Character based Identification keys - Qureshimatva, Umerfaruq; Gamit, Sandip B.; Solanki, Hitesh A. (Indian Forester, 2020)
Arecaceaec family is the third largest economically important family distributed mainly in tropics and sub-tropics. In India palms are mainly distributed in three geographical regions including the Peninsular India, forest areas of Northern India and Andaman and Nicobar Islands. In the present study 39 genera and 79 species with 31 cultivated varieties include ornamental, cultivated and wild palms were reported. Maximum diversity of palms found in Ahmedabad with 74 species followed by Vadodara 26 species, Gandhinagar 24 species, Surat 22 species and others are less than 22. The genera and species are arranged in according to phylogenetic classification of the Arecaceae proposed by Dransfield et al., 2005 for easy references. Article deal with identification key based on morphological characters. Each species carries the valid name and nomenclatural references which have been encounteredin updated APG III nomenclature system.